Evaluation of the Informational Content, Readability and Comprehensibility of Online Health Information on Monogenic Diabetes. Issue 3 (26th September 2017) - Guan, Yue; Maloney, Kristin A.; Roter, Debra L.; Pollin, Toni I.
Abstract: The purpose of this study was to assess the informational content, readability, suitability and comprehensibility of websites offering educational information about monogenic diabetes available to patients. The top 20 results from 15 queries in four search engines were screened. Content analysis was performed by two independent coders. Readability was determined using Flesch‐Kincaid grade level (FKGL) and Simplified Measure of Goobledygook (SMOG). The Comprehensibility Assessment of Materials (SAM + CAM) scale was utilized to evaluate website suitability and comprehensibility. Only 2% ( N = 29) of 1200 screened websites met inclusion criteria. Content analysis showed that 16 websites presented information on at least the most common forms of MODY (1, 2 and 3), four addressed the utility of genetic counseling, and none included support resources for patients. All websites exceeded the consensus readability level (6th grade) as assessed by FKGL (10.1 grade) and SMOG (12.8 ± 1.5 grades). Although the majority ( N = 20) of websites had an overall "adequate" to "superior" quality score (SAM + CAM score > = 40%), more than one‐third scored "not suitable" in categories of content, literacy demand, graphics, and learning motivation. The online educational resources for monogenic diabetes have a high readability level and require improvement in ease of use and comprehensibility for patients with diabetes.